Avaliação hidrogeoquímica dos reservatórios Jacarecica I e Macela situados na bacia hidrográfica do rio Sergipe, nordeste, Brasil - Lima, Maria Hortência Rodrigues (2020)
In this work, we studied the hydrogeochemical processes involved in the water chemical characteristics of the Jacarecica I and Macela reservoirs, situated in the Sergipe River hydrographic basin. Surface water samples were collected for each reservoir, in eight campaigns between 2013 to 2018, covering dry and rainy seasons. In each sample, the following parameters were determined: pH, temperature, electrical conductivity, total dissolved solids, sodium, potassium, calcium, magnesium, chloride, sulfate, and bicarbonate. The ionic abundance in the two reservoirs followed the following order: Na+ > Ca2+> Mg2+> K+ and HCO3- > Cl- > SO4 2- , whose waters were classified by Piper's diagram, as predominantly sodium and chlorinated. In Gibbs diagram, the Jacarecica I and Marcela reservoir samples occupied the region of the weathering domain, indicating that the water-rock interaction is the main mechanism that controls the geochemistry of the dissolved ionic constituents. Based on the ionic reasons, it was possible to infer that the main hydrogeochemical processes that control the water chemical characteristics were the dissolution of the minerals halite, calcite and K-feldspar, for the Jacarecica I reservoir and for the Macela reservoir, the dissolution of halite, dolomite, K-feldspar, with a significant contribution from the direct ion exchange process. The results of the inverse geochemical modeling, determined using PHREEQC, validated the hydrogeochemical processes deduced for the two reservoirs, based on the ionic ratios. Through modeling, it was also possible to identify that the main hydrogeochemical differences between the reservoirs are associated with the significant contribution of biotite, to the concentrations of magnesium in the water of Jacarecica I and the process of direct ion exchange for the concentrations of calcium and sodium in the water of the Macela reservoir. There is evidence that in both reservoirs, there are already anthropogenic impacts related to irrigated agriculture activities, requiring better management of these areas to minimize the problem of water salinization.